Biological and Genetic Characterization of Pod Pepper Vein Yellows Virus-Associated RNA From Capsicum frutescens in Wenshan, China - Peng, Jiejun; Bu, Shan; Yin, Yueyan; Hua, Mengying; Zhao, Kuangjie; Lu, Yuwen; Zheng, Hongying; Wan, Qionglian; Zhang, Songbai; Chen, Hairu; Liu, Yong; Chen, Jianping; et al. (Frontiers in Microbiology, 2021)
Tombusvirus-like associated RNAs (tlaRNAs) are positive-sense single-stranded RNAs found in plants co-infected with some viruses of the genus Polerovirus. Pod pepper vein yellows virus (PoPeVYV) was recently reported as a new recombinant polerovirus causing interveinal yellowing, stunting, and leaf rolling in Capsicum frutescens plants at Wenshan city, Yunnan province, China. The complete genome sequence of its associated RNA has now been determined by next-generation sequencing and RT-PCR. Pod pepper vein yellows virus-associated RNA (PoPeVYVaRNA) (GenBank accession No. MW323470) has 2970 nucleotides and is closely related to other Group II tlaRNAs, particularly Tobacco bushy top disease-associated RNA (TBTDaRNA, GenBank Accession No. EF529625). In infection experiments on Nicotiana benthamiana and C. frutescens, synergism between PoPeVYVaRNA and PoPeVYV was demonstrated, leading to severe interveinal yellowing of leaves and stunting of plants. The results provide further information on the genetic and biological properties of the various agents associated with pepper vein yellows disease.